LES CONFLITS ARMES ET VIOLATION DES DROITS DE L’ENFANT EN REPUBLIQUE DEMOCRATIQUE DU CONGO : Regard sur la Province de l’Ituri - Lucien Nongo Loshima, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The Ituri, former district of de Democratic Republic of Congo and one of the provinces newly created at the end of dismemberment are in prey to armed conflicts since two decades about. Among the vulnerable social categories the more touched, the children are confronted to recurrent cases of violation of their rights. Yet, the armed conflicts don't constitute in anything a reason of violation of the rights guaranteed so much by the legal instruments international that national. Paradoxically to this elementary principle, he/it clearly appears that the children in Ituri are the subject of inhuman and degrading treatments.